Analisis Kinerja Sistem Informasi SMK Swasta Pemda - Yuni Saputri; Marnis Nasution; Masrizal Masrizal (Jurnal Informatika, 2024)
This research aims to analyze the performance of the information system used in local government private vocational schools, which plays an important role in supporting the smooth operation of schools, including the teaching and learning process, administration and financial management. The research method used is benchmarking, which involves collecting data through interviews, observations and questionnaires. The research results show that the existing information system still has several weaknesses, such as lack of integration between systems, inaccurate data reporting, and low efficiency in data processing. Based on these findings, this research provides recommendations for improving the information system in local government private vocational schools to make it more effective and efficient in supporting school activities.